The effect of body mass index and waist circumference on selected important seminal parameters - Munasinghe, D.A.L.; Weerasooriya, B.; Liyanage, J.; Wakkumbura, H.P.; Manohara, M.G.R.K. (GSC Advanced Research and Reviews, 2023)
A cross sectional study was carried out in a fertility clinic of Sri Lanka in 2018 to find the relationship of body mass index and waist circumference with seminal parameters such as volume, count, motility and morphology of the male with fertility issues (n=105). The male infertility which can cause psychosocial issues, is rising in the modern society. Most of the etiologies of male infertility are unknown and could be biological in origin. Thus, the study was launched to achieve the target up to a certain extent. Every male who visited the clinic for fertility issues was personally evaluated on consent to gather the anthropometric and demographic data. Further, the semen samples of them were also collected for semen analysis. The effect of obesity (BMI and waist circumference wise) on each seminal parameter was tested separately with two statistical tests such as Spearman correlation and Wilcoxon signed rank test and found to have no significant effect from either BMI or waist circumference hence obesity on seminal parameters such as count, volume motility and morphology. Perhaps this could be due to finding of a smaller number of individuals who were in obese and extreme obese situations.
Keywords: BMI; Waist Circumference; Obesity; Seminal Parameters; Male infertility